2008
DOI: 10.1021/es702561t
|View full text |Cite
|
Sign up to set email alerts
|

NP1EC Degradation Pathways Under Oxic and Microxic Conditions

Abstract: The degradation pathway of nonylphenol ethoxyacetic acid (NP1EC) and the conditions favoring dicarboxylated alklyphenol ethoxyacetic acid (CAnP1EC; where n = the number of aliphatic carbon atoms) formation were studied in oxic microcosms constructed with organic carbon-poor soil from the Mesa soil aquifer treatment (SAT) facility (Arizona) and pristine organic carbon-rich sediments from Coyote Creek (California). Results suggest that the availability of dissolved oxygen determines the dominant biodegradation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The vertical position of a mass spectrometric group indicates the recalcitrance of its members to biodegradation by strain Bayram (group numbers-encircled numbers at the far right-are listed according to increased recalcitrance). sediments from California (Montgomery-Brown et al 2008). The results suggested that the oxygen tension determined the dominant biodegradation pathway.…”
Section: (B) Biotransformation Of Nonylphenoxyacetic Acidmentioning
confidence: 95%
See 3 more Smart Citations
“…The vertical position of a mass spectrometric group indicates the recalcitrance of its members to biodegradation by strain Bayram (group numbers-encircled numbers at the far right-are listed according to increased recalcitrance). sediments from California (Montgomery-Brown et al 2008). The results suggested that the oxygen tension determined the dominant biodegradation pathway.…”
Section: (B) Biotransformation Of Nonylphenoxyacetic Acidmentioning
confidence: 95%
“…Moreover, oxygen tension also seems to be an important factor in determining the reaction pathway of NPnEC. Under low oxygen tension, formation of CAPnEC is significant, whereas under high oxygen tension further metabolism via NP and subsequent ipso-substitution is favoured (Montgomery-Brown et al 2008).…”
Section: (D) New Views On Microbial Transformations Of Nonylphenolic mentioning
confidence: 98%
See 2 more Smart Citations
“…According to Jonkers et al (2001) and Di Corcia et al (1998), CAPECs started to accumulate after NPECs were formed during biotransformation of NPEOs. Montgomery-Brown et al (2008) has found that alkyl chain oxidation of NP 1 EC by microcosms and the formation of CAP 1 ECs is favored under microxic conditions. Thus, it may be possible that pathway 1 is favored by the microxic conditions.…”
Section: Gammaproteobacteria Betaproteobacteriamentioning
confidence: 99%